(untitled) (Malaysian Journal of Learning and Instruction, 2018)
Purpose – The aim of this study was to identify the level of Principals’ Technology Leadership and its five constructs namely Visionary Leadership, Digital Age Learning Culture, Excellence in Professional Practice, Systemic Improvement, and Digital Citizenship in schools. In addition, the relationship between Principals’ Technology Leadership and Teachers’ Technology Integration was measured. Besides that, the effect of Professional Development as a moderator of the mentioned relationship was also investigated. Methodology – Systematic random sampling was carried out to select 90 principals and 645 teachers in this cross-sectional survey. The Principals Technology Leadership Assessment (PTLA) which is based on National Education Technology Standards –Administrator, NETS-A (2009), and Survey of Technology Experiences’ were administered to principals, while the Learning with ICT: Measuring ICT Use in the Curriculum Instrument was administered to the teachers. Findings – The study showed that there was a significant relationship between Principals’ Technology Leadership and Teachers’ Technology Integration. Furthermore, Professional Development had a significant effect on the relationship between the two variables. Significance – Professional development emphasising ICT must be carried out for school principals so that they can become technology leaders and motivate teachers to integrate technology in the classroom to prepare students as skilled workers for Industrial Revolution 4.0.